Сhanges in the donor site following bone-patellar tendon-bone graft harvesting with open or closed defects - Pavel A. Trachuk; Aleksandr P. Trachuk; Oleg E. Bogopolskiy (Travmatologiâ i Ortopediâ Rossii)
Background. The patellar tendon is frequently used as a graft source for anterior cruciate ligament reconstruction. The search of the factors that enhance the healing process of the donor site may contribute to improved anatomical and functional outcomes.